Non-steady diffusion and adsorption of organic micropollutants in ion-exchange membranes: effect of the membrane thickness - Malgorzata Roman; Pawel Roman; Rhea Verbeke; Leonardo Gutierrez; Marjolein Vanoppen; Marcel Dickmann; Werner Egger; Ivo Vankelecom; Jan Post; Emile Cornelissen; Karel Keesman; Arne Verliefde (iScience, 2021)
Summary: There is no efficient wastewater treatment solution for removing organic micropollutants (OMPs), which, therefore, are continuously introduced to the Earth's surface waters. This creates a severe risk to aquatic ecosystems and human health. In emerging water treatment processes based on ion-exchange membranes (IEM), transport of OMPs through membranes remains unknown. We performed a comprehensive investigation of the OMP transport through a single IEM under non-steady-state conditions. For the first time, positron annihilation lifetime spectroscopy was used to study differences in the free volume element radius between anion- and cation-exchange membranes, and between their thicknesses. The dynamic diffusion-adsorption model was used to calculate the adsorption and diffusion coefficients of OMPs. Remarkably, diffusion coefficients increased with the membrane thickness, where its surface resistance was more evident in thinner membranes. Presented results will contribute to the improved design of next-generation IEMs with higher selectivity toward multiple types of organic compounds.